Parent question use during shared reading time: How does training affect question type and frequency?. Issue 2 (31st December 2018) - Zibulsky, Jamie; Casbar, Christine; Blanchard, Tamar; Morgan, Chelsea
Abstract: This study was designed to examine whether participation in a shared reading workshop alters the frequency with which parents ask their children questions during book reading sessions, particularly questions designed to strengthen component reading skills that they may not have known about before training. Participants in the reading workshop series ( N = 57) were taught strategies for asking questions about story content and word structure to build children's language and literacy skills. Findings suggest that parents may be somewhat familiar with traditional dialogic reading strategies focused on story content and utilize them without instruction, whereas parents may be less knowledgeable about sound or print‐focused skills and do not employ strategies focused on word structure until instructed to do so. It is also notable that parents do not use all story content prompts equally. This information can be used by school psychologists to refine the messages educators share with parents about how to best support their children's reading development.